Dental treatments performed under general anesthesia in a Pediatric Dentistry Department of a Teaching Dental Center. Retrospective study - Condori Cary, Yesmile Danny (2023)
Objective: To determine the frequency of dental treatments in patients of the Pediatric Dentistry service treated under general anesthesia at the Dental Teaching Center of Cayetano Heredia Peruvian University (CDC-UPCH) during the period 2016-2019. Material and Methods: This cross-sectional, retrospective, descriptive, and observational study was conducted on a sample of 54 medical records of children aged 3 to 12 years. The age and gender of the patients, place of origin, year of treatment, number of treated teeth, and the type and frequency of dental treatments performed were identified. Results: The sample consisted of 36 boys and 18 girls; 38.89% were between 3 and 6 years old, and 53.71% were between 7 and 12 years old. The most performed treatments were resin restorations (27%) and preformed stainless-steel crowns (18%), while surgery accounted for only 6.47%. Conclusion: Resin restorations and preformed stainless-steel crowns were the most frequent treatments in children treated under GA at the CDC-UPCH during the period 2016-2019. Most of dental treatments under general anesthesia were performed in children between 7 and 12 years old. However, the highest number of dental treatments was performed in children aged 3 to 6 years.